Myocardial T2* Mapping with Ultrahigh Field Magnetic Resonance: Physics and Frontier Applications - Huelnhagen, Till; Paul, Katharina; Ku, Min-Chi; Serradas Duarte, Teresa; Niendorf, Thoralf (Frontiers in Physics, 2017)
Cardiovascular magnetic resonance imaging (CMR) has become an indispensable clinical tool for the assessment of morphology, function and structure of the heart muscle. By exploiting quantification of the effective transverse relaxation time (T2*) CMR also affords myocardial tissue characterization and probing of cardiac physiology, both being in the focus of ongoing research. These developments are fueled by the move to ultrahigh magnetic field strengths, which permits enhanced sensitivity and spatial resolution that help to overcome limitations of current clinical MR systems with the goal to contribute to a better understanding of myocardial (patho)physiology in vivo. In this context, the aim of this report is to introduce myocardial T2* mapping at ultrahigh magnetic fields as a promising technique to non-invasively assess myocardial (patho)physiology. For this purpose the basic principles of T2* assessment, the biophysical mechanisms determining T2* and (pre)clinical applications of myocardial T2* mapping are presented. Technological challenges and solutions for T2* sensitized CMR at ultrahigh magnetic field strengths are discussed followed by a review of acquisition techniques and post processing approaches. Preliminary results derived from myocardial T2* mapping in healthy subjects and cardiac patients at 7.0 Tesla are presented. A concluding section discusses remaining questions and challenges and provides an outlook on future developments and potential clinical applications.